The intergrowth of YTa7O19 in L-Ta2O5 with Er3+/Yb3+ enhancing pure green upconversion luminescence intensity by molten salt synthesis - Fan, Yuhan; Cao, Yongze; Zhang, Zhihua; Tao, Hualong; Li, Meiling; Zhang, Xizhen; Xu, Sai; Chen, Baojiu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
By using the molten salt synthesis with B2O3 flux and adjusting the doping concentration of Y3+, the intergrowth of the YTa7O19 phase in L-Ta2O5 is achieved. This structure enhances the pure green upconversion luminescence (UCL) intensity, which is because the YTa7O19 phase isolates the distribution of Er3+/Yb3+ in the 2D layer, localizing the energy transfer from Yb3+ to Er3+ and reducing the loss during the energy transfer process. By adjusting the concentration of Er3+/Yb3+ and the holding temperature, the green UCL integral intensity of the optimal sample is 1.09 times that of β-NaYF4:Er3+/Yb3+. The intergrowth of the YTa7O19 phase in L-Ta2O5 is demonstrated by high-resolution transmission electron microscopy (HRTEM) and comparing bandgap values, and the structure and properties cannot be obtained by solid phase sintering. Using the luminescence intensity ratio (LIR) technology, the absolute temperature sensitivity (SA) and relative temperature sensitivity (SR) were 0.01359 K−1 and 0.01001 K−1, respectively. The phosphor-converted 980 nm LEDs based on samples are fabricated, the CIE color coordinate can reach (0.20, 0.76), which exceeds NTSC standard. This indicates that this material can be used for temperature sensing and luminescence display applications. •MSS achieved the intergrowth of YTa7O19 in L-Ta2O5.•Energy clustering improves the UCL intensity.•The UCL intensity of the optimal sample can reach 109 % of β-NaYF4:Er3+/Yb3+.•The CIE color coordinates of fabricated LED chip surpasses the NTSC color gamut.